Programmable editing of a target base in genomic DNA without double-stranded DNA cleavage - Komor, Alexis C.; Kim, Yongjoo B.; Packer, Michael S.; Zuris, John A.; Liu, David R. (Nature (London), 2016)
CRISPR/Cas9 DNA editing creates a double-stranded break in the target DNA, which can frequently generate random insertion or deletion of bases (indels); a new genome editing approach combining Cas9 with a cytidine deaminase is described here, which corrects point mutations more efficiently than canonical Cas9, while avoiding double-stranded breaks and indel formation. DNA edits without double-helix breakage The CRISPR/Cas technology widely used for genome editing involves formation of a double-strand break in the target DNA sequence. When used to modify a single nucleotide, this procedure frequently generates DNA insertions or deletions (indels). David Liu and colleagues describe an approach that obviates DNA cleavage, as a means to avoid such off-target mutations. This 'base editing' method, which utilizes a composite enzyme consisting of CRISPR/Cas9 and the APOBEC1 deaminase, can directly convert C to T (or G to A). They also describe modifications that increase the yield of the desired correction and significantly suppressing indel formation. Current genome-editing technologies introduce double-stranded (ds) DNA breaks at a target locus as the first step to gene correction 1 , 2 . Although most genetic diseases arise from point mutations, current approaches to point mutation correction are inefficient and typically induce an abundance of random insertions and deletions (indels) at the target locus resulting from the cellular response to dsDNA breaks 1 , 2 . Here we report the development of ‘base editing’, a new approach to genome editing that enables the direct, irreversible conversion of one target DNA base into another in a programmable manner, without requiring dsDNA backbone cleavage or a donor template. We engineered fusions of CRISPR/Cas9 and a cytidine deaminase enzyme that retain the ability to be programmed with a guide RNA, do not induce dsDNA breaks, and mediate the direct conversion of cytidine to uridine, thereby effecting a C→T (or G→A) substitution. The resulting ‘base editors’ convert cytidines within a window of approximately five nucleotides, and can efficiently correct a variety of point mutations relevant to human disease. In four transformed human and murine cell lines, second- and third-generation base editors that fuse uracil glycosylase inhibitor, and that use a Cas9 nickase targeting the non-edited strand, manipulate the cellular DNA repair response to favour desired base-editing outcomes, resulting in permanent correction of ~15–75% of total cellular DNA with minimal (typically ≤1%) indel formation. Base editing expands the scope and efficiency of genome editing of point mutations.